2019
DOI: 10.1101/591016
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MASST: A Web-based Basic Mass Spectrometry Search Tool for Molecules to Search Public Data

Abstract: Correspondence:We introduce a web-enabled small-molecule mass spectrometry (MS) search engine. To date, no tool can query all the public small-molecule tandem MS data in metabolomics repositories, greatly limiting the utility of these resources in clinical, environmental and natural product applications. Therefore, we introduce a Mass Spectrometry Search Tool (MASST) (https://proteosafe-extensions.ucsd.edu/masst/), that enables the discovery of molecular relationships among accessible public metabolomics and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…The benefit of using FBMN can be illustrated with the metal chelating agent ethylenediaminetetraacetic acid (EDTA), widely used in beauty products, food, and scientific protocols. A search for its occurrences in public spectral datasets with the mass spectrometry search tool (MASST) 24 showed that it is frequently observed in plasma samples where it is used during the sample preparation. We took one of the public human serum sample datasets ( MSV00008263 ) where EDTA was observed.…”
Section: Methodsmentioning
confidence: 99%
“…The benefit of using FBMN can be illustrated with the metal chelating agent ethylenediaminetetraacetic acid (EDTA), widely used in beauty products, food, and scientific protocols. A search for its occurrences in public spectral datasets with the mass spectrometry search tool (MASST) 24 showed that it is frequently observed in plasma samples where it is used during the sample preparation. We took one of the public human serum sample datasets ( MSV00008263 ) where EDTA was observed.…”
Section: Methodsmentioning
confidence: 99%
“…We demonstrated the ability to readily determine the location in which the chemical standards MS/MS spectrum selected via MSMS-Chooser were found using MASST. 11 Any additional MS/MS spectra uploaded to the GNPS MS/MS spectral library will be included in the periodic living data analysis in GNPS. Data submitters will be emailed when new chemical annotations are found in their MassIVE deposited data.…”
Section: Resultsmentioning
confidence: 99%
“…Upon completion of the job, the resulting file output of MSMS-Chooser should be checked manually for accuracy, and poor quality or incorrect spectra should be deleted (row-wise) from the results table. The MSMS-Chooser output was then used to generate the associated MS/MS library spectra which were subsequently uploaded to the GNPS MS/MS spectral library ( Figure 1D) 11 was performed on an illustrative compound, biotin, from the MSMS-Chooser results page (Figure S1). The illustrative MASST job can be accessed using the following link: https://gnps.ucsd.edu/ProteoSAFe/status.jsp?task=39cd886540c147e9a8a618b275e5f541.…”
Section: Msms-choosermentioning
confidence: 99%
“…Community adoption of GNPS has sharply increased the volume of MS data in the public domain 7 . It has also spurred new tools development (MASST 75 , FBMN 41 , ReDU 76 ) and enabled many biological discoveries. Due to the fundamental differences between CID and EI fragmentation, the GNPS infrastructure could not previously support the analysis of EI data.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, although GC-MS is the oldest and most established of MS-based methods, and the sheer volume of existing EI reference data accumulated over decades (far exceeding that for any other kind of MS), researchers still use decades-old data analysis strategies. We anticipate that the new GNPS community infrastructure will incentivize moving raw EI data into the public domain for data reuse, comparable to the trajectory for tandem MS 7,75,76 . GC-MS analysis within GNPS/MassIVE will lower the expertise threshold required for analysis, encourage FAIR practices 27 through reusable deposition of the data in the public domain, and promote data analysis reproducibility and “recycling” of GC-MS data.…”
Section: Discussionmentioning
confidence: 99%